The Effect of The Effectiveness of Parent Interpersonal Communication on Children's External Self-Concept During The Covid-19 Pandemic at SMA Pangudi Luhur II Servasius - Bekasi - Diadema, Sibilina; Ambarwati, Maria Francisca Lies (Journal of Multidisciplinary Issues, 2022)
Objective – Interpersonal communication in human life has an influence on many things, one of which is self-concept. A teenager still needs assistance from his parents in forming his self-concept so that his social environment and future can be guaranteed. This study aims to analyze the effect of the effectiveness of parental interpersonal communication on children's external self-concept during the COVID-19 pandemic at Pangudi Luhur II Servasius High School. Methodology – This research was conducted in September 2020 – January 2021. A quantitative method with a total sample of 261 people out of a total population of 558 people was used. Findings – Using the theory of the effectiveness of interpersonal communication, the theory of family communication patterns, and the theory of external self-concept, the result shows that there is a positive relationship between the effectiveness of parental communication and the child's external self-concept. The effectiveness of parental interpersonal communication affects the external self-concept by 9.2%. Novelty – This study examined the effectiveness of parental interpersonal communication on children's external self-concept during the COVID-19 pandemic. Keywords: Interpersonal Communication, Family Communication Patterns, Effectiveness of Communication, External Self-Concept.